Estudo taxonômico e anatômico em espécies de Canoparmelia s.l. (Parmeliaceae, Ascomycota liquenizados) - Zanetti, Camila Aparecida [UNESP] (2014)
Canoparmelia s.l. (Canoparmelia and Crespoa) is representative in open areas in cerrados and its ability to tolerate dry sunny environments contributes to the settlement of several species in urbanized areas. This work intended to describe the morphology of six species of Canoparmelia s.l., including the study of type specimens, the verification of chemical variability and a comparative study of thallus anatomy, looking for characteristics that can be used to support taxonomic studies in this group. The selected species were Canoparmelia caroliniana, C. cryptochlorophaea, C. texana, Crespoa carneopruinata, C. crozalsiana and C. scrobicularis. To perform the anatomical studies, samples of the material were fixed in FAA 50 and included in resin methacrylate, cut in rotary microtome, stained with toluidine blue and mounted on microscope slides with synthetic resin Entellan®. The protocol of anatomic description developed by the Lichenological Group of Studies (GEL) was used to describe the microscope slides. The protocol of morphological description also developed by the GEL was used to describe the specimens. Spot tests, UV fluorescence tests and thin layer chromatography were conducted to perform the chemical analysis. The type specimens were requested to LD, H, S, W and SP herbaria. The anatomical studies were efficient to reach the proposed objectives and revealed significant differences in the cortex and algal layer in the transversal sectioning of the studied species; these differences support the distinction between Canoparmelia and Crespoa. Some structures, such as the pseudocyphellae found in Crespoa scrobicularis and the haptera observed in Canoparmelia cryptochlorophaea require further studies. Chromatography showed that three specimens of C. texana have a chemical profile that differs from the type and probably belong to a new taxon. This work has shown that anatomy has an important role to the understanding of the development ...